An Analysis of English Teacher and Learner Talk in the Classroom Interaction - Shofiyatul Huriyah; Merie Agustiani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The objectives of the research were to find out the kinds of teacher talk and learner talk used by English teacherand learners during the classroom interaction and to know the language mostly used in the classroom. The participants of this study were 35 students and 1 English teacher that were taken using purposive sampling technique. This descriptive study used recording and interview in colecting the data. The results of clasroom interaction recording was then analyzed using Flander’s Interaction Analysis Categories (FIAC). It was obtained that teacher talk (75,5%) dominated the interaction during the classroom. In the interaction, the teacher mostly used ask question category (30,2%) meanwhile the learners mostly used pupil talk response category (9,1%). Furthermore, Indonesian language (57,2%) was dominantly used, while English was only 28,1%. From the research result, it can be concluded that the English teacher dominated the class by asking so many questions and mostly used Indonesian language during the classroom was taking place. It gave the students less chance to explore and practice their English. Keyword: teacher talk, learner talk, classroom interaction.